Proceso de atención de enfermería en paciente masculino de 18 años con trauma abdominal. - Valarezo Ávila, Romina Doménica (2021)
The following clinical case study is focused on an 18-year-old patient who was diagnosed in the emergency area with abdominal trauma, for presenting trauma characterized by a blunt object hit in the right costal region and a clinical picture of chronic pain due to abdominal trauma and limitation of the right lower limb. Once the patient was stabilized, the doctor ordered urinalysis, hematology and blood chemistry tests, plus cranial computed tomography, cervical and abdominal computed tomography with contrast. Patient is transferred to Surgery I area, to prepare for an exploratory laparotomy surgery. However, before continuing with the process of my clinical case, I must mention that my research emphasizes the causes, risk factors and complications that a patient entails before, during and after suffering an abdominal trauma. Therefore, as a health professional we are fully obliged to value the patient by putting all our senses when receiving the patient. And, above all, carry out a meticulous cephalocaudal assessment, in order to be able to match them to the patient's clinical picture and proceed to the elaboration of the Nursing Care Process according to the functional patterns that are altered and that compromise the patient's health status. In order to develop an ideal nursing care plan related to the needs required by the patient. Adequate monitoring and control will also be provided both to the patient and their needs, as well as to treatment and comfort. In the same way, the pertinent nursing care will be carried out, where the use of the taxonomies Nanda (diagnoses), Nic (interventions) and Noc (results) will be applied in order to fulfill our objectives proposed in this clinical case study.